Chiral Phosphoric Acid Catalyzed Asymmetric Cycloadditions: from Alkenes to Alkynes - Wang, Liu-Yang; Yang, Lan; Chen, Jie; Zhou, Ling (Synlett, 2023)
Organocatalytic asymmetric cycloaddition reactions are the foundation for the construction of important cyclic molecules in synthetic chemistry and biochemistry. As a result, organic catalysts, in particular chiral phosphoric acid, entice researchers from all over the world to design and develop asymmetric cycloaddition reactions. In this Account, we discuss CPA-catalyzed [3+2] and [4+2] cycloaddition of alkenes and some further transformations from the cycloadducts, as well as several mechanisms related to these cycloadditions. All kinds of enantioenriched carbocycles and heterocycles with stereogenic centers could be synthesized efficiently. Recent advances in CPA-catalyzed cycloaddition of alkynes to generate axially chiral compounds are also discussed.1 Introduction2 CPA-Catalyzed [3+2] Cycloaddition of Alkenes3 CPA-Catalyzed [4+2] Cycloaddition of Alkenes4 CPA-Catalyzed Cycloaddition of Alkynes5 Conclusions
Keywords: chiral phosphoric acid; organocatalysis; cycloaddition; alkenes; alkynes